Transformation of n-Heptane by Brønsted Acidic Sites Over 12-Tungstosilicic Acid - AOUISSI, AHMED (Asian Journal of Chemistry, 2010)
Catalytic transformation of n-heptane over H4SiW12O40·13H2O as a solid acid catalyst was investigated. The prepared heteropolyacid H4SiW12O40·13H2O was characterized by means of XRD and IR. Catalytic tests were carried out in a continuous flow system under atmospheric pressure. The effect of the reaction temperature and the support on the n-heptane transformation was investigated. It has been found that Brønsted acidic sites play an important role in n-heptane reaction. The lack of protons on the heteropolyacid owing to the collapse of the Keggin structure observed at 320 ºC led to a decay of the activity of H4SiW12O40· 13H2O. The decrease of the number of protons through a heteropolyacidsupport interaction favored the cracking reaction to the detriment of cyclization reaction.